Native plant and pollinator survey on an organic herb farm in Washington state - Mollema, Alyssa; Ragosta , Summer; Kruse, Danielle (Ethnobotany Research and Applications, 2025)
Background: Trout Lake Farm (TLF) is a certified organic herb farm in North America. Located in Trout Lake, WA, it supplies plant material to a leading nutritional supplement company. TLF’s main crops include Coneflower (Echinacea angustifolia DC., Echinacea purpurea (L.) Moench), Catnip (Nepeta cataria L.), and Common Dandelion (Taraxacum officinale F.H.Wigg). TLF is beginning to adopt the principles of regenerative agriculture, including the documentation and support of biodiversity on the farm’s property. The goal of this study was to provide a baseline understanding of pollinator habitat on farm property, as well as the proportion of native species found along the farm borders and field edges. Methods: The methods included random sampling of uncultivated areas on farm property for native and non-native plant species and cover, as well as sampling both cultivated and uncultivated areas on property for Lepidopteran (butterfly and moth) and Hymenopteran (bee and wasp) pollinators. Results: Results showed an estimated 8.3 percent of the farm’s property can be considered beneficial habitat for pollinators and other key wildlife. Pollinators were observed to be more abundant within the crop fields than in the uncultivated areas. The most abundant pollinator observed was the non-native honeybee (Apis mellifera), followed by native Bombus species and the Western Tiger Swallowtail (Papilio rutulus). Conclusions: TLF has a uniquely supportive relationship with native flora and fauna compared to traditional staple crop agricultural systems. Opportunities exist for increasing native habitat and improving sustainability practices. This initial evaluation of the farm’s biodiversity is the first step of supporting native species in an agricultural setting. Keywords: Regenerative agriculture, Uncultivated land, Working lands, Pollinator habitat, Organic farming, Native species